Conflicting Goals for Moral Education: A study of the behavioral intentions of teachers in Catholic secondary schools in the Netherlands - Hermans, Chris A.M. (International journal of education and religion, 2000)
This article examines the criticism from liberal educators that the goals of moral education in religiously affiliated schools are incompatible. This paper addresses whether it is true that teaching a religious community’s values is incompatible with the development of moral autonomy; that teaching civic values is incompatible with teaching Christian values; and that teaching Christian values is incompatible with introducing children to the plurality of value systems in our society. This research demonstrates that from the perspective of teacher’s behavioral intentions, these goals are not in conflict within Catholic schools of secondary education in the Netherlands. The article concludes with a reflection on the research results from an ethical perspective and from the perspective of philosophy of education